Perancangan Infografis Interaktif Bagi Pengunjung Museum Singhasari Malang - Denny Kurniawan; Adita Ayu Kusumasari; Jozua F Palandi (MAVIS : Jurnal Desain Komunikasi Visual, 2022)
Singhasari museum was building not only understand the legacy singosari kingdom but also singhasari museum has a strong and an opportunity in tour history. Yet singhasari museum has a lack of layouts in an information museum collection for want a media to have attention and information singhasari museum. This last project aims to produce an interactive and attractive design so that information can be properly. Yet the design method used by the author starts from the method of collecting data through observation, interviews, and documentation. Then proceed with the data analysis method using SWOT analysis (Strength, Weakness, Opportunity, Treatment) and then media planning and creative planning. In planning this interactive media, it displays layouts, typography, photography, and colors that are attractive and simple so that later information is well. By planning this interactive media, it is hoped that it will attract as well as become information about the Singhasari Museum.